Ustekinumab Demonstrates Lower Uveitis Risk in Moderate to Severe Psoriasis Patients Compared with Tumor Necrosis Factor-α Inhibitors - Chul Hwan Bang; Hyun Ju Oh; Yeong Ho Kim; Jin-Hyung Jung; Ji Hyun Lee; Young Min Park; Ju Hee Han (Medical Journals Sweden, 2024)
Abstract is missing (Short communication)